Geothermal resources for sustainable development: A case study. (6th March 2022) - Baba, Alper; Chandrasekharam, Dornadula
Summary: Turkey's primary energy source is fossil fuels, with a contribution of 55%. According to the International Energy Agency forecast, fossil fuels will continue to be the primary energy source for the next decade. The current CO2 emissions from fossil fuel‐based energy are 400 Mt. If the present energy usage trend continues, then the emissions will cross 500 Mt by 2030. However, Turkey has large scope to mitigate climate‐related issues and follow sustainable development agenda by increasing the share of geothermal energy as a primary energy source mix. The country established a strong geothermal energy program in 1984 by installing a 17 MWe geothermal power plant in Kızıldere and made tremendous progress in this field. Currently, the power generation has crossed 1665 MWe. Turkey has drawn a new road map to enhance its primary energy source mix by developing its radiogenic granites (Enhanced Geothermal Systems) for power generation and carbon dioxide capture programs. This is an emerging technology that is being recommended for Turkey. Currently, France, Australia, and the United Kingdom are surging ahead in implementing Enhanced Geothermal Systems (EGS), and France has established a pilot power plant using EGS and generating 10 MWe. The United Kingdom will be starting its 3 MWe power plant. The hydrothermal source, in combination with Enhanced Geothermal Systems, can contain the annual CO2 emissions to 500 Mt and reduce the per‐capita CO2 emissions to 4.5 tons annually. One of the greatest contributions to climate mitigation and sustainable development made by the geothermal industry is the sequestration of CO2 from the Kızıldere geothermal power plant for the manufacturıng of dry ice and use CO2 from the Tuzla geothermal power plant for minimizing scaling. This dry ice technology can be extended to the cement industry to capture 18 billion CO2 being emitted annually from clinker manufacturıng units. The dry ice will be useful in combating forest fires that are common in Turkey. The article discusses the new technological developments that Turkey is adopting to mitigate climate change and achieve sustainable development goals. Abstract : Turkey can move toward low carbon foot print based sustainable development approach by utilizing its hydrothermal and EGS sources and reduce CO2 emissions below the current 500 Mt and also reduce per‐capita CO2 emissions below 4.5 tons annually.